1999
DOI: 10.1177/026988119901300309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rolipram on the elevated plus-maze test in rats: a preliminary study

Abstract: The objective of the present study was to assess the behavioural effects of rolipram, a specific cAMP phosphodiesterase (PDE4) inhibitor, in the elevated plus-maze (EPM) test in rats. Results showed that rolipram at the highest dose tested (0.1 mg/kg) increased the percentage of both time spent and entries into open arms, although a decrease of locomotor activity in the EPM test was also observed. In contrast, diazepam (3.0 mg/kg) exhibited the typical profile of an anxiolytic in the EPM test, increasing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…They also may induce anxiogenic-like effects and sedation (Heaslip and Evans, 1995;Imaizumi et al, 1994;Silvestre et al, 1999b), although an anxiolytic-like effect also has been reported (Silvestre et al, 1999a). While studies have shown that PDE4D plays an important role in the mediation of antidepressant-like effect (Zhang et al, 2002) and may be involved in memory , the role of PDE4B has not been investigated due to the lack of highly selective inhibitors of individual PDE4 subtypes and the complexity of the PDE4 family in terms of its numerous variants and compartmentation (Conti et al, 2003;Houslay et al, 2005;Terrin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also may induce anxiogenic-like effects and sedation (Heaslip and Evans, 1995;Imaizumi et al, 1994;Silvestre et al, 1999b), although an anxiolytic-like effect also has been reported (Silvestre et al, 1999a). While studies have shown that PDE4D plays an important role in the mediation of antidepressant-like effect (Zhang et al, 2002) and may be involved in memory , the role of PDE4B has not been investigated due to the lack of highly selective inhibitors of individual PDE4 subtypes and the complexity of the PDE4 family in terms of its numerous variants and compartmentation (Conti et al, 2003;Houslay et al, 2005;Terrin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The reports to date are inconsistent. One study showed that the PDE4 inhibitor rolipram produced an anxiolytic-like effect in rats (Silvestre et al, 1999a), whereas Data shown represent the mean7SEM of 6-7 mice per group. The latency was the time before the animal descended to the grid floor where they had previously received a mild, inescapable footshock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During an elevated plus-maze test, the selective PDE4 inhibitor rolipram produces anxiolytic-like behavior in rats independent of simultaneous locomotor behavior (Silvestre, Fernandez et al 1999). Thought to originate as intracellular cAMP, extracellular cAMP levels detected by microdialysis in rats increase in right medial prefrontal areas in response to a restraint stressor or peritoneal saline injection stressor (Stone and John 1992).…”
Section: Camp In Stress and Anxietymentioning
confidence: 99%
“…Studies with rodents support the role of PDE4 in CNS processes including depression [89], learning and memory [90], and anxiety [91]. Studies using PDE4 inhibitors (rolipram and etazolate) demonstrate an antidepressant-like effect [92,93,94,95,96], a reversal of memory deficits [97,98,99] and a reduction in anxiogenic behavior [100,101,102,103]. Amplification of the cAMP pathway with type IV-specific PDE inhibitor rolipram [90,97,104,105] increased the long-term but not the short-term memory of contextual fear conditioning and object recognition (table 1).…”
Section: Direct/indirect Inhibition Of the Pka Pathway: Lessons From mentioning
confidence: 99%